AN ANALYSIS OF SEGMENT INSERTION, ADD NEW FEATURE, AND PHONEME CHANGE OF THE INDONESIAN PRONOUNCED BY KOREAN YOUTUBER - Maghfiroh, Ismi Ainul; Andayani, Sri; Wafa, Hosnol (JURNAL LITERASI, 2023)
This research aims to describe the segment insertion, add new feature, and phoneme change of the Indonesian pronounced by Korea Reomit, Ujung Oppa, and Bandung Oppa as Korean YouTuber. The research design in this study is a descriptive qualitative method. The data collection methods used in this research are observation, listening, and note-taking. The contents used in this research are nine video contents. For the nine YouTube short contents are 80 pieces of data from three Korean YouTubers. The result of 80 data includes 16 data on segment insertion, 44 data on add new feature, and 20 on phoneme change. But, at the first subject, no phoneme change was found. Based on the amount of data, the dominant data was found at the add new feature. The result of this study is the segment insertion, add new feature, and phoneme change were found at the object of this research.